A new genus and species of the scale insect family Qinococcidae (Hemiptera: Coccomorpha) from China - Zheng, Xinyi; Wu, San’an (Zootaxa, 2023)
A new genus of Qinococcidae, Abrococcus Zheng & Wu gen. n. is established for a new species Abrococcus cunninghamia Zheng & Wu sp. n., which was collected on Cunninghamia lanceolata (Cupressaceae) from Guizhou Province, P. R. China. Descriptions and illustrations are provided for the adult female and first-, second- and third-instar female nymphs. Keys to the adult females and first-instar nymphs of the genera of Qinococcidae and known developmental stages of A. cunninghamia are provided.